Didactic Model: Teaching the English Temporal System to Arabic Freshman Learners of English - Thana Hmidani (Profile: Issues in Teachers' Professional Development)
This study took place at a medical college with 57 Arabic first-year students taking an intensive English course. The aim was to address the problems that learners experience when using the English tenses properly. The didactic model was developed and implemented in the study group only (27 students). Pre, mid-, and post-tests were administered to study and control groups at three points in time. The model is a selection of aspects from different methods combined aiming to lead participants to a higher level of linguistic competence in terms of language awareness, reading and writing skills, and vocubulary building. The results indicated statistically significant differences in the post-test between the two groups over time regarding the level of linguistic competence.